Statistically Determining the Spatial Extent of Relativistic Electron Precipitation Events Using 2‐s Polar‐Orbiting Satellite Data. Issue 4 (17th April 2021) - Gasque, L. Claire; Millan, Robyn M.; Shekhar, Sapna
Abstract: Relativistic electron precipitation (REP) from the outer radiation belt into Earth's atmosphere poses risks for satellites and affects Earth's climate, producing ozone‐destroying compounds. Characterizing the spatial extent of REP events, which are periods of precipitation localized in space and time, is important for quantifying these effects and improving understanding of outer radiation belt dynamics, allowing quantification of the relative roles of atmospheric and magnetopause particle loss. Following Shekhar et al. (2017, https://doi.org/10.1002/2017JA024716), who used 16 s resolution data from particle detectors onboard NOAA's Polar‐orbiting Operational Environmental Satellites (POES) and the ESA's Meterological Operational (MetOp) Satellites, we work to more precisely determine the spatial extent of REP events using higher‐resolution (2 s) data from the same instruments. We algorithmically search through 6 years of data (October 2012 to December 2018) from a maximum of seven simultaneously orbiting satellites, identifying REP events and determining their start and end times and locations. We find that the majority of events are highly localized spatially and, unlike Shekhar et al. (2017, https://doi.org/10.1002/2017JA024716), we do not observe a cluster of broad events around midnight magnetic local time (MLT). Based on case studies, we suggest that this discrepancy results from the differences in data resolution, indicating that the broad regions of precipitation around midnight MLT identified by Shekhar et al. (2017, https://doi.org/10.1002/2017JA024716) may be composed of several adjacent but narrowly confined regions of precipitation, potentially with independent causes. Additional work is necessary to further classify events and identify their likely mechanisms. Key Points: Relativistic electron precipitation (REP) events detected using POES/MetOp 2 s data show the expected distributions in L and magnetic local time (MLT) The 2 s data offers greater spatial resolution than in previous studies, and reveals that REP events are narrow in L shell Spatial structure during long midnight REP events may point to multiple mechanisms acting around midnight MLT